Spatial filtering of radiation from wire lasers. (21st February 2017) - Orlova, E E; Solyankin, P M; Angeluts, A A; Lee, A; Kosareva, O G; Ozheredov, I A; Balakin, A V; Andreeva, V A; Panov, N A; Aksenov, V N; Shkurinov, A P
Abstract: In this letter we propose an approach to obtain directive radiation from wire lasers with subwavelength transverse dimensions and length much larger than the radiation wavelength (wire lasers) based on spatial filtering of their radiation using a combination of a spherical lens and a diaphragm. Theoretical modeling based on the antenna model for wire lasers shows that a directive beam with the uniform phase front can be formed when the diaphragm separates the maximum of the image field of the laser created by the lens. We demonstrate spatial filtering of wire laser radiation experimentally using a terahertz quantum cascade laser.